The Relationship between Low Newborn Baby Weight (Bblr) and the Incident of Neonatal Asphyxia - Zahra (Benih : Journal of Midwifery, 2022)
Low birth weight (LBW) is a significant factor contributing to neonatal asphyxia, a critical condition occurring during the neonatal period. This study aims to investigate the correlation between LBW and the incidence of neonatal asphyxia at Permata Madina General Hospital, located in Panyabungan District, Mandailing Natal Regency in 2023. Employing an analytical survey method with a cross-sectional approach, the study population comprised 48 patients at the hospital. Samples were selected using a total sampling technique. Data analysis involved univariate and bivariate analyses, including frequency distribution and the Chi-Square test. Results revealed that 20 respondents (41.7%) had low birth weight babies, with the majority of cases of neonatal asphyxia occurring in this group (15 respondents, 31.3%). Statistical analysis indicated a significant relationship between LBW and neonatal asphyxia at Permata Madina General Hospital in 2023, with a p-value of 0.002 (p<0.05). The findings suggest that babies with low birth weight are at greater risk of experiencing asphyxia compared to those with normal birth weight. The study emphasizes the importance of enhancing the quality of healthcare services in hospitals to facilitate early detection and treatment of LBW infants, thereby reducing the incidence of neonatal asphyxia among this vulnerable population.